Sports hip injuries : diagnosis and management - Kelly, Bryan, 1968-; Bedi, Asheesh, 1978-; Larson, Christopher M., 1968-; O'Sullivan, Eilish (SLACK Incorporated, 2015)
In the world of sports, hip injuries among an athletic population can be very difficult to diagnose and manage. That's why Sports Hip Injuries: Diagnosis and Management is a comprehensive guide to diagnosing and managing sports hip injuries and hip preservation. Drs. Bryan Kelly, Asheesh Bedi, Chris Larson, and Eilish O'Sullivan have been or currently are team physicians for various professional sports teams and are leaders in the field of hip preservation. They present Sports Hip Injuries: Diagnosis and Management in a concise manner by focusing on hip and pelvis disorders and cover all the typical disorders seen in athletes presenting with hip and pelvic pain. The anatomy, presentation, clinical evaluation, imaging, nonsurgical and surgical treatment, and post-surgical rehabilitation of hip joint disorders are presented clearly throughout. Some of the topics include: Femoroacetabular impingement, Hip instability/dysplasia, Athletic pubalgia/core muscle injury, Stress fractures and traumatic sports injuries of the hip and pelvis, Myotendinous injuries and nerve entrapment disorders of the hip and pelvis, Rehabilitation guidelines and return-to-sport outcomes. Sports Hip Injuries: Diagnosis and management is an invaluable resource for sports medicine providers including orthopedic surgeons and fellows that care for patients presenting with hip pain for athletes at all levels, as well as physical therapists and athletic trainers. -- from back cover.